2014
DOI: 10.1017/s0021859614001154
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on maize and winter wheat yields in China from 1961 to 2010 based on provincial data

Abstract: The impacts of climate change on maize and winter wheat yields in China from 1961 to 2010 were studied in the current paper, based on provincial data. The results indicated that rising average temperatures resulted in decreased maize yield in most of the study regions, and reduced maize production at a national scale by c. 3·4% relative to the average from 1961 to 2010. Moreover, the warming resulted in a decrease of winter wheat yield in the Huang-Huai-Hai and southwest regions and led to an overall loss in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Besides environmental factors, quality and quantity of grain yields are determined by the crop genetic yield potential and by agronomic measures of crop management that aim to reduce environmental limitations. Despite the ongoing advancement in breeding for higher grain yields since the 1960s, the use of nitrogen fertilizers, irrigation or pesticides, the steady increase of winter wheat ( Triticum aestivum L.) yields during the second half of the 20th century has slowed down since the 1990s in several regions of the globe (Brisson et al, 2010; Calderini & Slafer, 1998; Chen, Zhou, & Pang, 2015; Grassini, Eskridge, & Cassman, 2013; Laidig, Piepho, Drobek, & Meyer, 2014). For instance, historical yield records reveal that winter wheat yields almost simultaneously reached a plateau at about 7–8.5 t/ha in many West European high‐yield countries between 1991 and 2000 (Brisson et al, 2010; Grassini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Besides environmental factors, quality and quantity of grain yields are determined by the crop genetic yield potential and by agronomic measures of crop management that aim to reduce environmental limitations. Despite the ongoing advancement in breeding for higher grain yields since the 1960s, the use of nitrogen fertilizers, irrigation or pesticides, the steady increase of winter wheat ( Triticum aestivum L.) yields during the second half of the 20th century has slowed down since the 1990s in several regions of the globe (Brisson et al, 2010; Calderini & Slafer, 1998; Chen, Zhou, & Pang, 2015; Grassini, Eskridge, & Cassman, 2013; Laidig, Piepho, Drobek, & Meyer, 2014). For instance, historical yield records reveal that winter wheat yields almost simultaneously reached a plateau at about 7–8.5 t/ha in many West European high‐yield countries between 1991 and 2000 (Brisson et al, 2010; Grassini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures can reduce photosynthetic enzyme activity, destroy the chloroplast structure, and close stomata, all of which affect photosynthesis (Zhang et al ., 2010; Ponce et al ., 2013; Shen and Wang, 2013; Xiao et al ., 2013; 2016; Chen et al ., 2015; Zhang et al ., 2015). In the current study, the crop photosynthesis rate of the potato–broad bean–winter wheat rotation system was significantly decreased when the temperature increased by 0.5–2.0°C in the podding stage of broad bean and the heading, blooming and booting stages of winter wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Fogarasi et al [37] showed that slightly decreasing yields is projected for the next three decades for winter wheat and maize. Decrease of diurnal air temperature range resulted in 2.9% decrease in maize winter wheat production in China from 1961 to 2010 [38]. Table 4.…”
Section: Winter Wheat Evapotranspirationmentioning
confidence: 99%